New Database for Foundation and Ground Performance in Liquefaction Experiments. Issue 4 (November 2015) - Allmond, Jacquelyn; Kutter, Bruce L.; Bray, Jonathan; Hayden, Connor
Physical modeling of buildings founded on layers of liquefiable sand has produced insightful data describing ground and building performance. A new publicly available NEEShub database, "FLIQ, " summarizes data from 9 large-scale centrifuge tests with 4 different lead experimentalists, various soil profiles, 49 stations of site and structure response, and more than 60 shaking events, that is, 405 events in total. Example correlations between ground-motion intensity measures and performance measures are presented to illustrate the usefulness of the database. The relationship between PGA at the surface and base is highly variable when liquefaction is observed; however, the relationship between the cumulative absolute velocity ( CAV ) at the surface and base is relatively linear, even when liquefaction occurs. Additionally, the CAV was found to correlate well with settlement and can account for settlement history. Contrary to intuition, foundation settlement in liquefied soil is not directly correlated to bearing pressure; larger bearing pressures can decrease liquefaction occurrence and related settlements. The database has potential to grow through future community input.